Michel Kikoine and Rezekne - Lisov, Alexander (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Michel (Mikhaпl) Kikoпne (1892-1968) is one of the artists of the School of Paris, the school, represented by the great number of names of Jewish emigration from Russia. The creative manner of Kikoпne formed in Paris under the influence of P. Cezanne’s and P. Bonnard’s painting. Kikoпne is most often mentioned (in the past and actually) as one of the famous Parisian trio of artists issued from Vilna school of drawing and painting of I. P. Trutnev: Ch. Soutine, P. Krйmиgne, M. Kikoпne. Krйmиgne and Kikoпne for many years rested in the shadow of the creativity of Soutine, and only in the last decade, the interest to them, referred to the second row of the famous representatives of the School of Paris, has increased significantly. Early biographies of all members of this trio reveal a great deal of similarities and notable parallels. In reference biographical articles of European publications they often called “Litvak”, call them the “French painters of the Lithuanian origin” (more correctly, “Litvak-born French painters”). “Litvak”, as it is well known, is the name of a territorial and linguistic subgroup of Ashkenazi Jews widespread on the territory of the provinces of the Russian Empire, actually parts of modern Lithuania, Latvia and Belarus. The information about the birth of M. Kikoпne in various publications is quite confused and contains a lot of contradictions. The testimony of the artist himself and of the members of his family could be estimated critically. Among the authors of his biographies there is no consensus about his origin, and it convinces of the importance of archival research. In an early biography of Kikoпne, in reports of his family tree is constantly mentioned the town of Rezekne. A statement of a genealogical problem, a more detailed study of early biography of the artist involves many questions about his connection with Rezekne. In view of insufficient level of study of the archive’s material, author attempts in the present article only to plan some questions those arise during the reading of the Michel Kikoпne’s biography. The experience of biographical studies of other well-known Jewish artists affirmed themselves in the European art centers at the beginning of the 20th century, such as M. Chagall, O. Zadkine, and Ch. Soutine, shows and proves that clarification and documental proof of whole the complex of biographical data of the artist is necessary. Trying to gain a foothold in the Paris artistic beau monde, the natives from the Russian Jewish shtetl of the Pale often “altered” their biographies, creating the improved versions, in seeking to raise their social status. In certain cases, the documents of birth, issued by local community rabbis, were forged. Often, the year of birth was changed in order to avoid the conscription. Thus, in the case of the biography of Michel Kikoпne, as, indeed, of many other immigrants, residents of Paris’ “The Hive” (“La Ruche”), to be confirmed at least the most important, basic biographical facts. The article examines the disputable questions about the date and place of birth of Michel Kikoпne, about the origin and professional activities of his father, about relations of the artist with the town of Rezekne.